A haze-free ASEAN : will the vision go up in smoke? - Yang Razali Kassim (2014)
ASEAN ministers meet in Kuala Lumpur this week for urgent talks to tackle the latest haze problem in Indonesia that has choked neighbouring countries. Concrete plans must be made to work to prevent the vision of a haze-free ASEAN going up in smoke.